The sense of agency in joint actions: A theory-driven meta-analysis. (March 2022) - Zapparoli, Laura; Paulesu, Eraldo; Mariano, Marika; Ravani, Alessia; Sacheli, Lucia M.
Abstract: The sense of agency is the feeling of voluntarily controlling our actions and their effects. It represents a crucial component of self-awareness, and it is foundational to our perception of responsibility toward what we do as individuals acting in a social context. While the sense of agency has been widely investigated in individual contexts, much less is known about the agency experienced when subjects are involved in motor interactions, despite its relevance in the social domain. To fill this gap, here we review the literature on the sense of agency experienced during motor interactions. We aimed to test the reliability of this sense of joint agency across studies and define what features can modulate its explicit and implicit components. To this end, we performed a formal meta-analysis of studies investigating the implicit feeling of agency in joint actions and a systematic review of studies addressing explicit judgments of agency during motor interactions. Our review indicates that, during interactions, a sense of agency can also be experienced for the partner's actions, both at an implicit and explicit level, and that this possibility strongly depends on predictive sensorimotor mechanisms. Contextual cues play a crucial role too, but mainly on explicit agency judgments, while they do not affect the implicit feeling of agency. These results are discussed in light of current cognitive theories on motor awareness and motor interactions. We also propose a hierarchical model based on recursive predictive and comparative processes whereby the sense of joint agency is grounded on a weighted combination of sensorimotor and contextual cues. Finally, we discuss how this model may provide a framework for future research in the social and clinical domains.